2020
DOI: 10.1093/ehjci/jeaa175
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular myocardial work in the culprit vessel territory and impact on left ventricular remodelling in patients with ST-segment elevation myocardial infarction after primary percutaneous coronary intervention

Abstract: Abstract Aims Adverse left ventricular (LV) remodelling after ST-segment elevation myocardial infarction (STEMI) is associated with poor outcome. Global and regional LV myocardial work (LVMW) derived from speckle tracking echocardiographic strain data in combination with non-invasive blood pressure recordings could provide information for prediction of LV remodelling after STEMI. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 29 publications
3
17
0
1
Order By: Relevance
“…This is concordant with Khurelsukh et al (24) who found non-significant difference between the study group regarding culprit MI territory whether anterior or non-anterior STEMI. On the contrary this was discordant with Lustosa et al (25) who found that, the regional values of MWI and MWE in the culprit vessel territory of LAD and LCx were significantly lower in patients with early LV remodeling compared to patients without early LV remodeling. These discrepancies with our study might be explained by the small sample size of our study design.…”
Section: Discussionsupporting
confidence: 57%
“…This is concordant with Khurelsukh et al (24) who found non-significant difference between the study group regarding culprit MI territory whether anterior or non-anterior STEMI. On the contrary this was discordant with Lustosa et al (25) who found that, the regional values of MWI and MWE in the culprit vessel territory of LAD and LCx were significantly lower in patients with early LV remodeling compared to patients without early LV remodeling. These discrepancies with our study might be explained by the small sample size of our study design.…”
Section: Discussionsupporting
confidence: 57%
“…In our cohort, the MWI and MCW increased significantly after intervention. Recent studies have demonstrated in patients with anterior ST-elevation myocardial infarction who received PCI that MW is an independent predictor of LV recovery and early adverse LV remodeling ( 40 , 41 ). MW may be a useful tool to monitor the myocardial function during the short- and long-term follow-up of patients after PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Meimoun et al demonstrated that constructive work was the best parameter to predict segmental and global LV recovery after anterior ST elevation myocardial infarction (STEMI) and that patients with in-hospital complications had more severely impaired GCW (p < 0.01) [45]. In STEMI patients treated with percutaneous coronary intervention (PCI), lower values of global and segmental work index in the territory of the culprit lesion were associated with early remodeling of the LV [46]. Finally, MW has been applied in stress echocardiography examinations revealing statistically significant segmental decrease of work index in cases of inducible ischemia and inability of GWI increase, which was in contrast to healthy subjects where GWI increased by 54% [47].…”
Section: Coronary Artery Diseasementioning
confidence: 99%